Several rAAV Vectors Efficiently Cross the Blood–brain Barrier and Transduce Neurons and Astrocytes in the Neonatal Mouse Central Nervous System - Zhang, Hongwei (Nature Publishing Group, 2011)
Noninvasive systemic gene delivery to the central nervous system (CNS) has largely been impeded by the blood–brain barrier (BBB). Recent studies documented widespread CNS gene transfer after intravascular delivery of recombinant adeno-associated virus 9 (rAAV9). To investigate alternative and possibly more potent rAAV vectors for systemic gene delivery across the BBB, we systematically evaluated the CNS gene transfer properties of nine different rAAVEGFP vectors after intravascular infusion in neonatal mice. Several rAAVs efficiently transduce neurons, motor neurons, astrocytes, and Purkinje cells; among them, rAAVrh.10 is at least as efficient as rAAV9 in many of the regions examined. Importantly, intravenously delivered rAAVs did not cause abnormal microgliosis in the CNS. The rAAVs that achieve stable widespread gene transfer in the CNS are exceptionally useful platforms for the development of therapeutic approaches for neurological disorders affecting large regions of the CNS as well as convenient biological tools for neuroscience research.